Diagnosis and clinical implication of collision gastric adenocarcinomas: a case report - Hiromitsu Imataki; Hideo Miyake; Hidemasa Nagai; Yuichiro Yoshioka; Norihiro Yuasa; Junichi Takamizawa; Ayami Kiriyama; Masahiko Fujino (Surgical Case Reports)
Abstract Background Collision tumors are a subtype of simultaneous tumors wherein two unrelated tumors collide or infiltrate each other. Collision gastric adenocarcinomas (CGA) are rare and difficult to diagnose, and their clinical implications remain unclear. Herein, we aimed to reveal diagnostic methods for CGA and provide insight into its implications. Case presentation Among 1041 cases of gastric cancers (GCs) resected between 2008 and 2018, we included cases of confirmed CGA. Patients’ backgrounds, preoperative endoscopy findings, macroscopic imaging findings, and histopathology findings [including immunostaining for CK 7, MUC2, and mismatch repair (MMR) proteins] were investigated. The incidence of CGA was 0.5%: 5 of 81 cases having simultaneous multiple GCs. Tumors were mainly in the distal stomach. The CGA in two cases was between early cancers, in two cases was between early and advanced cancers, and in one case was between advanced cancers. There were three cases of collision between differentiated and undifferentiated types and two cases between differentiated types. Immunostaining with CK7 and MUC2 was useful for diagnosing collision tumor when the histology was similar to each other. Among ten GCs comprising CGA, nine tumors (90%) exhibited deficient MMR proteins, suggesting high microsatellite instability (MSI). Conclusions CGA is rare and usually found in the distal stomach. Close observation of shape, optimal dissection, and detailed pathological examination, including immunostaining, facilitated diagnosis. CGAs may have high MSI potential.